Digital Services Act: The Holy Grail of Cybersecurity? - Byczyński, Michał (Teisė, 2025)
This article explores the potential of the Digital Services Act (DSA) as a pioneering model for global digital governance. DSA, introduced by the European Union, seeks to establish a robust regulatory framework that addresses the complexities of the digital age, with a focus on platform accountability, transparency, and the protection of user rights. Through its comprehensive provisions, DSA aims to standardize approaches to content moderation, tackle disinformation, and enhance user privacy, thus setting new standards for digital responsibility. The article examines DSA’s alignment with the fundamental human rights, emphasizing its capacity to inspire similar regulations worldwide. By promoting transparency, safeguarding freedom of expression, and fostering cross-border regulatory cooperation, DSA demonstrates a holistic approach that could guide international efforts in cybersecurity and digital governance. This study underscores DSA’s potential to influence global regulatory practices, offering insights into how it may foster a safer and more accountable digital ecosystem on an international scale. On the other hand, it highlights the fundamental challenges of attempting to implement a DSA-like agreement on a global scale.